Does the Linkage between GDP, Renewable Energy, and Methane Validate the EKC hypothesis? Evidence from Indonesia - Destiartono, Mohamad Egi; Firmansyah, Firmansyah (International Journal of Energy Economics and Policy, 2024)
Is it feasible for Indonesia to sustain economic growth while simultaneously reducing methane emissions? This paper aims to unravel the Environmental Kuznets Curve (EKC) hypothesis for methane by integrating the role of renewable energy by employing annual data for the period 1990-2020. Autoregressive distributed lag (ARDL)-bounds testing is applied to estimate the dynamic and cointegration relationships. Also, this paper performs both traditional and breakpoint unit root tests. The EKC hypothesis is confirmed since there is an inverse U-curve nexus between GDP and methane per capita. The income turning point is 14,516 USD per capita. Indonesia’s income level is still below its estimated EKC threshold, implying that economic growth forces methane emissions to scale up. A 1% increase in GDP per capita leads to a 4.59% increase in methane per capita. However, renewable energy has a beneficial role in tackling methane emissions. A 1% increase in the share of renewable energy use leads to a 0.36% decrease in methane per capita. It is therefore recommended that to mitigate the damaging impact of economic growth, governments should enhance the share of energy use from renewable sources.